Conjugation of Steroidal and Non â€" Steroidal Anti- Inflammatory Drugs as Possible Mutual Prodrug - Muthanna D. Saud (College of Pharmacy University of Baghdad, 2017)
Prednisolone (SAID) was conjugated with ibuprofen (NSAID) through an amino acid (glycine) as a spacer arm to synthesize the following compound: Prednisolone â€" glycine â€" ibuprofen.     The method employed consists of converting the carboxylic acid function of (R,S) â€" ibuprofen â€" glycine to the highly reactive acid chloride and subsequent reaction with the C21 hydroxyl group of prednisolone. This reactive intermediate was found to react as well with the C17 tertiary hydroxyl group of the steroid to form three compounds and eight diastereomers. These results were confirmed by T.L.C, and the desired compound was separated by column chromatography. The identity of the prepared compound was established using U.V spectroscopy, IR spectroscopy and elemental microanalysis.The partition coefficient (PC) for this compound was estimated and found to be more soluble in the organic phase (n â€" octanol). Preliminary kinetic study indicated that the compound needs more than 15 hours for significant hydrolysis in phosphate buffer pH 7.8.